2016
DOI: 10.1161/jaha.115.002989
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Reduction With Ivabradine Protects Against Left Ventricular Remodeling by Attenuating Infarct Expansion and Preserving Remote‐Zone Contractile Function and Synchrony in a Mouse Model of Reperfused Myocardial Infarction

Abstract: BackgroundIvabradine selectively inhibits the pacemaker current of the sinoatrial node, slowing heart rate. Few studies have examined the effects of ivabradine on the mechanical properties of the heart after reperfused myocardial infarction (MI). Advances in ultrasound speckle‐tracking allow strain analyses to be performed in small‐animal models, enabling the assessment of regional mechanical function.Methods and ResultsAfter 1 hour of coronary occlusion followed by reperfusion, mice received 10 mg/kg per day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
(113 reference statements)
0
14
0
Order By: Relevance
“…Considering RM as a potential target for treatment strategies, several studies have demonstrated the beneficiary effects of therapeutic approaches, for example inducing a reduced heart rate, [ 22 ], anti-apoptotic effects in RM [ 23 ] or remodeling prevention via an angiotensin–AT1-receptor-dependent mechanism [ 24 ]. Further explorations of RM strain characteristics and their features as targets of pharmacological treatment are necessary in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Considering RM as a potential target for treatment strategies, several studies have demonstrated the beneficiary effects of therapeutic approaches, for example inducing a reduced heart rate, [ 22 ], anti-apoptotic effects in RM [ 23 ] or remodeling prevention via an angiotensin–AT1-receptor-dependent mechanism [ 24 ]. Further explorations of RM strain characteristics and their features as targets of pharmacological treatment are necessary in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments on AMI (Heusch & skyschally A et al., 2008; Mulder & BarbierS, 2004; O'Connor et al., 2016) showed that ivabradine slowed heart rate to improve the local blood flow in ischemic myocardium and systolic function, and thus reducing myocardial ischemic area. Priti et al (Priti et al., 2017) found that ivabradine is as effective as metoprolol in inferior AMIT patients, reducing the risk of first‐ or second‐degree atrioventricular block.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidences of rst and second degree atrioventricular block were signi cantly higher in the metoprolol group than in the ivabradine group. In the ischemia-reperfusion mouse model, O'Connor DM 8 showed that ivabradine could signi cantly improve ventricular remodeling by reducing the ventricular rate and heart rate variability. In a myocardial infarction and diabetes rat model, Cao X 9 showed that ivabradine could signi cantly reduce the uptake of norepinephrine in the myocardium and the plasma level of brain natriuretic peptide.…”
Section: Introductionmentioning
confidence: 99%